Code Of Ethics & Code Of Conduct And Employee Satisfaction In Order To Improve Employee Performance At The KANWIL DJP Jawa Barat I - Tedy Ginanjar K.I; Welly Surjono; Saepudin Saepudin (Jurnal Ekonomi Manajemen Perbankan, 2019)
Human resources is one of the assets that has an important role for the organization, namely its ability to contribute and optimal work performance such as the development or improvement of the code of ethics, professional ability, dedication, initiative, sense of responsibility, and employee performance.This research was conducted to find out, describe and analyze the code of ethics & code of behavior and employee satisfaction in order to improve employee performance in Kanwil DJP Jabar I.The method used is an associative descriptive method. The sample taken was 94 respondents. Data processing and analysis is  using statistical methods.Based on data processing, it is obtained that R = 0.769 means that the relationship between the code of conduct & the code of conduct and employee satisfaction with employee performance is strong. While kd = 0.591, it means that the code of ethics & code of conduct (X1) contribute 0.270 and employee satisfaction (X2) contribute 0.321 to employee performance (Y) and the rest of 0.409 is influenced by other factors not examined. With simultaneous testing results obtained F count = 65,813> F table = 3,099. Thus the hypothesis is rejected and accepted, this means that the code of ethics & code of behavior and employee satisfaction can improve employee performance in the Kanwil DJP Jabar I.